1989
DOI: 10.1111/j.1365-2125.1989.tb05347.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infused adenosine on cardiac output and systemic resistance in normal subjects.

Abstract: 1 The purine nucleoside adenosine relaxes smooth muscle in vitro and is a vasodilator in animals, but its effects on cardiac output and systemic vascular resistance have not been measured in normal conscious human subjects. 2 We have studied the effects of infused adenosine in doses of 0.005, 0.03 and 0.07 mg kg-l min-' on pulmonary blood flow and systemic vascular resistance in eight healthy volunteers, using a non-invasive, inert gas method and mass spectrometry.3 At a dose of 0.07 mg kg-' min-', there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 21 publications
(32 reference statements)
1
11
1
Order By: Relevance
“…Dose-dependent decreases in SVR and increases in cardiac output have been observed in conscious subjects (Bush et al, 1989), but reflexlymediated increases in heart rate occur, and at higher doses, subjective symptoms such as nausea and pain, may limit the clinical utility of adenosine (Edlund et al, 1989). Clinical evaluations of AMP have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Dose-dependent decreases in SVR and increases in cardiac output have been observed in conscious subjects (Bush et al, 1989), but reflexlymediated increases in heart rate occur, and at higher doses, subjective symptoms such as nausea and pain, may limit the clinical utility of adenosine (Edlund et al, 1989). Clinical evaluations of AMP have not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Current pharmacological data do not support the involvement of A 2 receptors in anxiety [277], or either receptor isoform in psychosis, but blockade of adenosine clearance produced antipsychotic effects in rats [278]. Adenosine agonists cannot be used as treatments, as they reduce cardiac output [170]. This effect was not observed when CBD was administered to either humans or animals; therefore, it is likely that CBD causes an indirect elevation of adenosine release as opposed to receptor activation.…”
Section: Cbd Receptor Targets In Psychosismentioning
confidence: 98%
“…Ttype VGCC α1G (CACNA1G) subunit expression is significantly increased in Purkinje cells in rodent models of ataxia, which results in the abnormal regulation of motor function [168]. Numerous studies on rodent models have also shown that palatal, Parkinsonian, and essential tremors are all dependent on T-type VGCC conductance [169,170]. Tremors were abolished upon channel blockade by zonisamide, a selective T-type VGCC antagonist [171].…”
Section: Cbd Ion Channel Targets In Movement Disordersmentioning
confidence: 99%
“…In contrast to these observations, it has been found that adenosine increases contractility of the isolated rabbit heart (33) and ventricular preparations from the guinea pig heart (32). Adenosine infusion was also found to increase the cardiac output in normal subjects and in patients with coronary disease (25,26,34). On the other hand, it has been shown that adenosine produced no inotropic effect in isolated guinea pig ventricles (35).…”
Section: Statistical Analyses Of Resultsmentioning
confidence: 97%
“…It was found to dilate the isolated coronary arteries of various species (19)(20)(21) and to increase the coronary blood flow several fold (22). A number of studies have also shown that the continuous intravenous infusion of adenosine markedly reduced the systemic vascular resistance and mean arterial blood pressure in experimental animals (23,24) and in humans (25,26). Furthermore, adenosine has been shown to cause vasodilatation in canine (27), porcine (28), bovine (20) and human (29) isolated vascular smooth muscle strips.…”
Section: Statistical Analyses Of Resultsmentioning
confidence: 99%